The influence of German borrowings from the field of fashion on the Upper Silesian dialect - Tomecka, Magdalena (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The entire Upper Silesian dialect is based on the Polish language system, and all elements from German are treated as borrowings. The main aim of the research was to focus on the issue of German loanwords in the field of clothing vocabulary that appear in the Upper Silesian dialect and which are listed in the “Dictionary of Silesian dialect” by Barbara and Adam Podgórski. The question of the assimilation of these borrowings was analysed on three levels: morphological, graphic and semantic.